Jupiter's X‐Ray and UV Dark Polar Region. Issue 11 (7th June 2022) - Dunn, W. R.; Weigt, D. M.; Grodent, D.; Yao, Z. H.; May, D.; Feigelman, K.; Sipos, B.; Fleming, D.; McEntee, S.; Bonfond, B.; Gladstone, G. R.; Johnson, R. E.; et al.
Abstract: We present 14 simultaneous Chandra X‐ray Observatory (CXO)‐Hubble Space Telescope (HST) observations of Jupiter's Northern X‐ray and ultraviolet (UV) aurorae from 2016 to 2019. Despite the variety of dynamic UV and X‐ray auroral structures, one region is conspicuous by its persistent absence of emission: the dark polar region (DPR). Previous HST observations have shown that very little UV emission is produced by the DPR. We find that the DPR also produces very few X‐ray photons. For all 14 observations, the low level of X‐ray emission from the DPR is consistent (within 2‐standard deviations) with scattered solar emission and/or photons spread by Chandra's Point Spread Function from known X‐ray‐bright regions. We therefore conclude that for these 14 observations the DPR produced no statistically significant detectable X‐ray signature. Plain Language Summary: Jupiter produces the most powerful ultraviolet (UV) and X‐ray aurorae in the solar system. While the UV and X‐ray aurora of the planet have each been explored independently, previous work exploring the spatial connection between Jupiter's X‐ray and UV aurorae was limited to a single simultaneous Chandra X‐ray Observatory (CXO) and Hubble Space Telescope (HST) observation from 2003. Since 2016, the arrival of the Juno spacecraft at Jupiter has led to extensive observing campaigns with CXO and HST, resulting in many new simultaneous X‐ray‐UV observations. Here, we present the analysis of 14 simultaneous CXO and HST observations of Jupiter's Northern aurorae from 2016 to 2019. While much of the emission from these bright aurorae is dynamic, there is one region that is dim for all 14 observations: Jupiter's dark polar region. Previous observations of this region have shown that it produces very little UV light. However, the extent to which X‐ray light is produced by the region remained unexplored and could provide the key to identifying why the region is so dark and what this tells us about the Jovian system. Across these 14 observations, we find that the region produces no significant X‐ray emission. Key Points: We compare 14 simultaneous Chandra X‐ray Observatory and Hubble Space Telescope UV observations of Jupiter's Northern Aurorae We detect no statistically significant X‐ray emission from the UV dark polar region (DPR) The DPR expands and the X‐ray and UV emission on the swirl region boundary shifts when the aurora show solar wind compression morphology